Nurturing wheat resilience: An overview of unravelling the detrimental effects of drought and heat stress (HS) on plant growth and grain quality and mitigation approaches for sustainable agriculture - Deepika Kathuria; Narpinder Singh; Sheetal Thakur; Tammana Awasthi; Swasti Mudgal (Environment Conservation Journal)
A substantial portion of the worldwide population relies on wheat as a foundational dietary staple. However, the increased occurrence and severity of drought and heat stress events due to climate change pose significant threats to wheat production. The physiological and biochemical responses of wheat to drought and heat stress (HS) varied and had unfavorable impacts on plant growth, as well as grain yield and quality. Understanding these responses is crucial for developing effective mitigation strategies. The high temperature during grain synthesis alters the synthesis and proportion of major chemical constituents in the grain, thereby affecting its functionality and suitability for processing into various products. Developing drought-tolerant and heat-resistant wheat varieties through marker-assisted breeding and genetic engineering are two modern strategies that effectively combat temperature stress. Additionally, agronomic practices such as improved irrigation methods, crop rotation, and precision farming are common approaches to enhance wheat resilience under stress conditions. This review serves as a valuable resource for researchers, agronomists, policymakers, and processors by providing a comprehensive overview of the effects of drought and HS on wheat growth and its grain quality and by offering insights into promising strategies for sustainable wheat production and its processing. Adapting and implementing these strategies are essential steps towards ensuring global food security, safeguarding the livelihoods of wheat-growing farmers, and shedding light on changes in the composition and functionality of wheat grain that are useful for the food industry.